Code Mixing and Interference in the Arabic Conversation of Non-Arabic Speakers/ اختلاط الرموز والتداخل اللغوي في الاتصال باللغة العربية للناطقين بغيرها - Luqmanul Yahya (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
The purpose of this research is to explain: (1) Code mixing and influencing factors in students' Arabic conversation at Mamba'us Sholihin boarding school. (2) Interference and influencing factors in the Arabic conversation of students at the Mamba'us Sholihin boarding school. This research uses qualitatively described method. The result of this study is (1) Code mixing in student communication in the form of code mixing between Arabic with Javanese, Madura and other foreign languages. factors that influence the occurrence of code mixing are different ethnic and cultural factors, habitual factors carried by the mother language and limited vocabulary mastery factors. (2) Interference in student communication there are three forms of interference, namely phonology, morphology and syntax. And the factors that influence the occurrence of interference are linguistic and non-linguistic factors.